Mind the gap, Dash & Lily - Cohn, Rachel; Levithan, David (Alfred A. Knopf, 2020)
"Dash and Lily were feeling closer than ever...it's just too bad they're now an ocean apart. After Dash gets accepted to Oxford University and Lily stays in New York to take care of her dogwalking business, the devoted couple are struggling to make a long distance relationship work. And when Dash breaks the news that he won't be coming home for Christmas, Lily makes a decision: if Dash can't come to her, she'll join him in London. It's a perfect romantic gesture...that spins out of Lily's control. Soon Dash and Lily are feeling more of a gap between them, even though they're in the same city. Will London bring them together again--or will it be their undoing?"--Back cover.